Middle East and North Africa Economic Monitor, October 2018 : A New Economy for Middle East and North Africa - Arezki, Rabah; Mottaghi, Lili; Barone, Andrea; Fan, Rachel Yuting; Harb, Amani Abou; Karasapan, Omer M.; Matsunaga, Hideki; Nguyen, Ha; de Soyres, Francois (Washington, DC: World Bank, 2018)
Growth in the Middle East and North Africa (MENA) region is projected to rebound to an average of 2% in 2018, up from an average 1.4% in 2017. The modest rebound in growth is driven mostly by the recent rise in oil prices, which has benefitted the region’s oil exporters while putting pressure on the budgets of oil importers. The rebound also reflects the impact of modest reforms and stabilization efforts undertaken in some countries in the region. The report forecasts that regional growth will continue to improve modestly, to an average of 2.8% by the end of 2020 while there is the ongoing risk that instability in the region could worsen and dampen growth. Despite recovery, the slow pace of growth will not generate enough jobs for the region’s large youth population. New drivers of growth are needed to reach the level of job creation required. The report offers a roadmap for unlocking the enormous potential of the region’s large and well-educated youth population by embracing the new digital economy. Broader and bolder reforms will be needed to achieve this goal, along with critical investments in digital infrastructure. It will require the reorientation of education systems toward science and technology, the creation of modern telecommunications and payments systems, and a private-sector driven economy governed by regulations that encourage rather than stifle innovation.